Aristotle’s exegesis of Parm. 28B16DK - Aguirre De la Luz, Nazyheli (Revista Archai, 2022)
The starting point for this study is the passage in Metaphysics, in which Aristotle quotes Parmenides’ fr. 28B 16 DK, which is analyzed in the light of other parallel passages within the Corpus Aristotelicum, as well as through the confrontation with Theophrastus’ comment in the De Sensibuson this same Parmenides’ fragment, in order to attempt, through an exhaustive lexical and semantic examination, a reconstruction of the interpretation that the Stagirite provided for Parmenides’ approach to certain psychic functions (sensory perception and / or cognition). In line with this analysis, we will also try to assess the objectivity of the critique that Aristotle addressed to the philosophical views contained in Parmenides’ poem.